Micro-Finance for Poor and Non-Poor Communities of Nepal - Dhakal, Chandra Prasad (Tribhuvan University Journal, 2018)
The micro-finance institutions are providing service to the people with the noble purpose to improve their socio-economic status which ultimately helps to reduce the poverty Nepal. In the Nepalese context, micro-finance institutions are providing the equal services to all people living in the remote and rural areas. The main objective of this study was to identify the economic importance of micro-finance institutions for poor and non-poor communities of Nepal. The study was conducted in Syangja district among the 385 beneficiaries of micro-finance. This study found that there was no significant association between the poor and non-poor people regarding the success of small scale business with the support of micro-finance, and increasing the amount of saving because p = .524 and .402 respectively which was greater than .05 significant levels. The difference could be observed in the increase in income level of poor and non-poor. Slight better improvement could be seen among the poor people, there was significant association between poor and non-poor because of p = .019.